PERANCANGAN PROMOSI MUSEUM BATIK INDONESIA UNTUK GENERASI MUDA MELALUI INSTAGRAM - Rashad, Mochammad; Susanti, Elizabeth; Tjandra, Miki (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2022)
Batik is a traditional Indonesian fabric with a blend of art and technology that has been recorded by UNESCO as one of the intangible world heritages. The Indonesian Batik Museum was established by the government to preserve, provide insight, and understanding of Nusantara batik to the public. To keep up with the times, museums are currently more focused on the visitor experience and not just as a repository of collections. However, at this time, there is still a lack of public interest in visiting and a lack of promotion on Museum Batik Indonesia’s social media. Hopefully, after visiting Museum Batik Indonesia, the mindset of visitors about Indonesian batik will change. The purpose of this promotional design is to increase the interest of the younger generation in visiting the Museum Batik Indonesia. Batik is Indonesia’s proud asset and deserves to be preserved, so it is necessary to introduce the history, meaning and various types of batik to the younger generation. Museum Batik Indonesia is a facility that can include education about Indonesian batik. The promotion design of Museum Batik Indonesia is using the AIDA (Awareness, Interest, Desire, Action) marketing strategy on Instagram. The design of this promotion includes various information about Museum Batik Indonesia and knowledge about batik in general, which is expected to increase the interest of the younger generation to wear, understand and love Indonesian batik.